2023
DOI: 10.1007/s00415-023-11807-x
|View full text |Cite|
|
Sign up to set email alerts
|

Neurological update: non-motor symptoms in atypical parkinsonian syndromes

Piriyankan Ananthavarathan,
B. Patel,
S. Peeros
et al.

Abstract: Among people with Parkinson’s disease (PD), non-motor symptoms (NMS) are a well-recognised cause of significant morbidity and poor quality of life. Yet, it is only more recently that NMS have been recognised to affect the lives of patients with atypical parkinsonian syndromes in a similar fashion. The aim of this article is to highlight and compare the relative prevalence of NMS among patients with atypical parkinsonian syndromes in the published literature, which largely remain underreported and unaddressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 125 publications
0
4
0
Order By: Relevance
“…Actually, most patients presented with either MSA-P or MSA-C, but signs of autonomic failure are always present [ 3 , 16 ]. It showed that urinary tract symptoms were present in 79.7% of the MSA patients [ 17 ]. Nonetheless, our findings indicate an elevated susceptibility to urinary system disorders, such as urinary tract infections, among patients with MSA-P rather than in patients with MSA-C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, most patients presented with either MSA-P or MSA-C, but signs of autonomic failure are always present [ 3 , 16 ]. It showed that urinary tract symptoms were present in 79.7% of the MSA patients [ 17 ]. Nonetheless, our findings indicate an elevated susceptibility to urinary system disorders, such as urinary tract infections, among patients with MSA-P rather than in patients with MSA-C.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these patients may be promptly referred to a urologist even for subtle urological disorders. On the other side, urological symptoms associated with MSA were frequently mistaken for benign prostatic hyperplasia symptoms, resulting in unnecessary urological surgery [ 17 ]. It is not clear whether this factor contributes to the elevated incidence of prostatic hyperplasia as well.…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic PD (iPD) is a typical progressive neurodegenerative condition that affects approximately 1% of adults over the age of 65 [ 27 ]. The following conditions can mimic iPD called atypical Parkinsonism: multiple system atrophy (MSA), corticobasal degeneration (CBD), progressive supranuclear palsy (PSP), and dementia with Lewy bodies (DLB) [ 29 , [35] , [36] , [37] ]. Other causes of Parkinsonism include secondary causes, such as vascular Parkinsonism (VaP) and drug-induced Parkinsonism, genetic causes, tremor disorders, and non-neurological differentials of PD [ 29 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The motor symptoms involve trembling and a lack of energy in the hands and legs, constipation, difficulty doing daily tasks, and a shuffled gait when walking [2]. Parkinson's disease non-motor symptoms include a variety of problems, including weariness, constipation, difficulty speaking, memory loss, and exhaustion [3]. Studies suggest that voice problems arise in about 90 percent of PD cases [4].…”
Section: Introductionmentioning
confidence: 99%